Avaliação da modulação do receptor purinérgico P2Y12 pelo clopidogrel no crescimento de células de glioma - Vargas, Pedro (2017)
Glioblastoma multiform (GBM) is considered the most aggressive tumors of central nervous system (CNS), and the most lethal among primary tumors presenting low survival prognosis, resistance to radiotherapy and chemotherapy. P2Y12 is considered a chemoreceptor for adenosine diphosphate (ADP). Its expression is documented in some cancer types, such as the C6 lineage of rat glioma, renal carcinoma and colon carcinoma. However, its role in the development of tumour progression and the resistance mechanism in chemotherapy are not well elucidated. Currently, it is well established that normal platelet function is an important factor for the progression of tumors, with thrombocytopenic rats demonstrating a significant reduction of metastases. Clopidogrel bisulfate is a drug, which belongs to the class of antiplatelet agents, being a P2Y12 receptor antagonist whose endogenous ligand is ADP. The aim of the present study was to determine the effects of tumor cells exposed to the treatment with clopidogrel. The C6 rat cell line was sensitive to the drug tested (150 μM) in the viability and cell counts (69.63 ± 8.70) and (53.05 ± 20.06). Both cell lines showed a significant reduction in the number of colonies after 10 days of treatment with clopidogrel. The U251-MG strain demonstrated a significant increase in the G1 phase and a significant reduction in the S phase in the cell cycle (20.32 ± 3.05) and (19.45 ± 2.35) in the concentration of 500 μM. Other results demonstrate important antiproliferative activity in both tumor lines, suggesting an important participation of the P2Y12 receptor in this process.